Macromol. Rapid Commun. 8/2014. Issue 8 (April 2014) - Roth, Peter J.; Davis, Thomas P.; Lowe, Andrew B.
<x xml:space="preserve">Abstract</x> Back Cover: Well‐defined poly[pentafluorophenyl (meth) acrylate] homopolymers are prepared by RAFT radical polymerization mediated by a novel chain transfer agent containing two cholesteryl groups in the R‐group fragment. Subsequent reaction with a series of small‐molecule amines in the presence of an appropriate Michael acceptor for ω‐group end‐capping yields a library of novel bischolesteryl functional hydrophilic homopolymers. Two examples of statistical copolymers are also prepared including a biologically relevant sugar derivative. Specific examples of these homopolymers are examined with respect to their ability to self assemble in aqueous media—a process driven entirely by the cholesteryl end groups. In all instances evaluated, and under the preparation conditions examined the homopolymers aggregate clearly forming polymersomes spanning an impressive size range Further details can be found in the article by P. J. Roth, T. P. Davis, and A. B. Lowe* on page 813. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>